The risk of synoptic-scale Arctic cyclones to shipping - A. F. Vessey; K. I. Hodges; L. C. Shaffrey; J. J. Day (Natural Hazards and Earth System Sciences, 2024)
The risk posed by Arctic cyclones to ships has seldom been quantified due to the lack of publicly available historical Arctic ship track data. This study investigates Arctic ship tracks derived from automatic identification system (AIS) transponders from September 2009 to December 2016. These are analysed with historical synoptic-scale cyclone tracks derived from ERA-5 reanalysis data and reports of past Arctic shipping incidents. We determine the number of ship tracks that intersected with intense Arctic cyclones tracks and how many of these intersections resulted in a reported shipping incident. The number of ships operating in the Arctic has increased year-on-year from 2010 to 2016. The highest density of ships occurs year-round in the Barents Sea. Trans-Arctic shipping transits via the Northern Sea Route and the Northwest Passage are limited to summer and autumn months, when sea ice extent has retreated sufficiently from the coastlines. Ship track density along these trans-Arctic routes is far less than the thousands of ships travelling in the Barents Sea year-round. Between 2010 and 2016, 158 Arctic shipping incidents were reported, but only 6 % of these reported incidents occurred following the passage of an intense Arctic cyclone. Arctic cyclones with significant wave heights greater than 6 m are found to frequently intersect ships, but only 0.1 % of these intersections resulted in a reported shipping incident. Results from this study indicate that ships are frequently impacted by Arctic cyclones, but cyclones were not a dominant cause of reported Arctic shipping incidents between 2010 and 2016. This suggests that ships are resilient to the rough sea conditions that past Arctic cyclones have caused, therefore mitigating and reducing risk.